General anesthesia in early infancy accelerates visual cortical development - Laurel J. Gabard-Durnam; Sarah A. McCormick; Ellen Underwood; Alice Tao; Isabelle Kim; Siobhan Coffman; Lindsay Benster; Maria Graziano; Charles A. Nelson; Charles B. Berde; Laura Cornelissen; Takao K. Hensch (Proceedings of the National Academy of Sciences, 2025)
How human brain function is established through protracted trajectories of development is not yet fully understood. Maturation of γ-aminobutyric acid (GABA) circuits drives critical periods of cortical development in animal models. Whether early functional inhibition similarly impacts the pace of human brain development remains unknown. Here, in a longitudinal study of 93 infants across a range of repeated exposures to general anesthesia shortly after birth, we observed a dramatically accelerated development of visual evoked potential (VEP) waveforms (but not their latency) consistent with a conserved biological mechanism across species. Such sequelae of prolonged GABA-active anesthesia in the first half year after birth may particularly impact those at-risk of altered excitatory–inhibitory circuit balance.